Mengungkap Cara Melakukan Praktik Fraud di Pemerintah Kota Malang - Ramadhani, Annas Rahmat; Triyuwono, Iwan; Purwanti, Lilik (Universitas Muhammadiyah Surakarta, 2019)
This study aims to reveal fraud practices in the government environment, especially in Malang City Government. The study uses an interpretive approach with ethnomethodology method developed by Garfinkel to find ways or methods that are believed in a social environment based on social interactions in daily life. The data in this study were obtained from observations in the field by actively participating in each activity, in-depth interviews related to ways to commit fraud in Malang City Government with people who are related and has direct contact with fraud, and using documentation based on irregularities documents. Data analysis was performed using indexicality and reflectivity analysis. The results of the study show that there are four ways to conduct fraudulent practices in Malang City Government, such as; giving gifts, Bancakan, misuse of the budget starting from the preparation to accountability, and embezzling government assets into private property. The results of this study confirm that fraud practices Malang City Governement depend on its socio-geographical conditions where the culture habits of the “Bahasa Walikan” and the “Oyi Tok Wes” phrase support fraud.